2011
DOI: 10.1158/1541-7786.mcr-10-0463
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin-c Splicing Isoform Contributes to Ovarian Cancer Progression

Abstract: Ovarian carcinoma is one of the most aggressive gynecological diseases and generally diagnosed at advanced stages. Osteopontin (OPN) is one of the proteins overexpressed in ovarian cancer and is involved in tumorigenesis and metastasis. Alternative splicing of OPN leads to 3 isoforms, OPNa, OPNb, and OPNc. However, the expression pattern and the roles of each of these isoforms have not been previously characterized in ovarian cancer. Herein, we have evaluated the expression profiling of OPN isoforms in ovarian… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
77
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 49 publications
12
77
1
Order By: Relevance
“…However, OPN-c expression dramatically reduced cell adhesion, and the authors suggest that OPN isoforms have distinct effects on cell behaviour but can work together to promote EAC progression (60). This is consistent with the clinical evidence described above suggesting that both OPN-b and OPN-c are overexpressed in some cancers, for example pancreatic (69,74), gastric (70), lung (74), and prostate (73), while OPN-c may be most strongly associated with other cancers, such as breast cancer (64,74,75) and ovarian cancer (76).…”
Section: Osteopontin Splice Variantsevidence For Association With Spesupporting
confidence: 77%
“…However, OPN-c expression dramatically reduced cell adhesion, and the authors suggest that OPN isoforms have distinct effects on cell behaviour but can work together to promote EAC progression (60). This is consistent with the clinical evidence described above suggesting that both OPN-b and OPN-c are overexpressed in some cancers, for example pancreatic (69,74), gastric (70), lung (74), and prostate (73), while OPN-c may be most strongly associated with other cancers, such as breast cancer (64,74,75) and ovarian cancer (76).…”
Section: Osteopontin Splice Variantsevidence For Association With Spesupporting
confidence: 77%
“…18 Recently, Tilli and colleagues demonstrated that the isoform OPN-c is specifically expressed in ovarian tumor samples and significantly activates OvCar-3 cell proliferation, migration, invasion, anchorageindependent growth and tumor formation in vivo. 19 These results demonstrate that different OPN transcripts have distinct roles that may be associated with their distinct roles in host defense and tumor process. Whether OPN transcripts have different roles in breast cancer formation in vivo and whether OPN transcripts expressed by tumor cells have distinct functions on immune cell differentiation are unknown.…”
Section: Introductionmentioning
confidence: 79%
“…Most recently, it has been reported that OPN-c specifically activated ovarian tumor cell proliferation, migration, invasion, anchorage-independent growth and tumor formation in vivo. 19 With consideration of the high level of OPN expressed by tumor cells, we constructed lentiviral expression vectors driven by a strong constitutive promoter and compared the function of all three OPN transcripts in breast cancer in vivo. We found that the overexpression of OPN transcripts significantly induced tumor growth possibly by promoting proliferation and preventing apoptosis of tumor cells; however, there was no significant difference among the three transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…OPN mRNA and/or protein expression levels were reported to be increased in several types of human cancers, such as prostate carcinoma (11); melanoma (12); and ovary (13), lung and gastric carcinoma (14). OPN overexpression was associated with poor prognosis in some malignancies, namely, in PTC (15).…”
Section: Introductionmentioning
confidence: 99%